Adverse Events Detection Through Global Trigger Tool Methodology: Results From a 5-Year Study in an Italian Hospital and Opportunities to Improve Interrater Reliability. Issue 6 (September 2021) - Mortaro, Alberto; Moretti, Francesca; Pascu, Diana; Tessari, Lorella; Tardivo, Stefano; Pancheri, Serena; Marta, Garon; Romano, Gabriele; Mazzi, Mariangela; Montresor, Paolo; Naessens, James M.
Abstract : Objective: Global Trigger Tool (GTT) has been proposed as a low-cost method to detect adverse events (AEs). The validity of the methodology has been questioned because of moderate interrater agreement. Continuous training has been suggested as a means to improve consistency over time. We present the main findings of the implementation of the Italian version of the GTT and evaluate efforts to improve the interrater reliability over time. Methods: The Italian version of the GTT was developed and implemented at the San Bonifacio Hospital, a 270-bed secondary care acute hospital in Verona, Italy. Ten clinical records randomly selected every 2 weeks were reviewed from 2009 to 2014. Two-stage interrater reliability assessment between team members was conducted on 2 subsamples of 50 clinical records before and after the implementation of specific review rules and staff training. Results: Among 1320 medical records reviewed, a total of 366 AEs were found with at least 1 AE on 20.2% of all discharges, 27.7 AEs/100 admissions, and 30.6 AEs/1000 patient-days. Adverse events with harm score E and F were respectively 58.2% (n = 213) and 38.8% (n = 142). First round interrater reliability was comparable with other international studies. The interrater agreement improved significantly after intervention (κ interrater I = 0.52, κ interrater II = 0.80, P < 0.001). Conclusions: Despite the improvements in the interrater consistency, overall results did not show any significant trend in AEs over time. Future studies may be directed to apply and adapt the GTT methodology to more specific settings to explore how to improve its sensitivity. Abstract : Supplemental digital content is available in the text.